Fish species caught in Cemisgezek Region of Keban Dam Lake and their amount - Dartay, Murside; Duman, Erdal (Ege Univ, 2006)
This study was done in Cemisgezek region of Keban Dam Lake, between February 2003 and April 2004. The purpose of this research way to determine the fish species and subspecies caught Cemisgezek region and their amount. As a result of the study five fish species and subspecies were caught during the fishing season (February 2003 - April 2004) from Cemisgezek region of Keban Dam Lake, yielding a total 137.939 tons (14.44 kg/hectare/year).
Keywords: Keban Dam Lake; Cemisgezek; Fish amount